"Constructive tensions" in resilience research: Critical reflections from a human geography perspective. Issue 1 (22nd September 2017) - Wilson, Geoff A.
Abstract : This review paper critically examines four "constructive tensions" in current resilience research, the first three of which are: its association with the roots of the resilience concept in ecological research; issues surrounding resilience as a normative or neutral concept; and confusion about the often interchangeable use of "resilience" and "sustainability" as possibly synonymous terms. The paper refers to these ambiguities as constructive tensions which have sparked fruitful discussions and debates. A fourth constructive tension is directly associated with human geography's engagement with resilience, especially by addressing the relative aspatiality of "mainstream" resilience research, by reinforcing the importance of power and agency in resilience processes, and by arguing that resilience is strongly associated with neoliberal pathways of development. The discussion highlights that much ambiguity remains surrounding some of the key concepts associated with what makes a system "resilient". This means that philosophical, moral and epistemological differences in natural‐science‐led and social‐science‐led resilience research need to be continuously acknowledged, and that mainstream resilience researchers can greatly benefit from critical insights offered by human geographers.